A Methodological Study of Qibla Direction Determination in Mar?q?l Al-'Ub?diyah: The Perspectives of Astronomical Science (Falak) and Islamic Jurisprudence (Fiqh) of Syekh Nawawi Al-Bantani - Muhammad, Naila Arifa; Ahmad Izzuddin; Iqbal Muhammad (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2025)
This research examines the methods for determining the Qibla direction in the book Maraqil Ubudiyah by Sheikh Nawawi al-Bantani, which combines principles of Islamic jurisprudence with traditional astronomical observations. The study focuses on the Ainu al-Kibla and Qaidah Mutsallatsah methods described in the book. Using a qualitative descriptive-analytical approach, data were gathered from the book's text, supporting literature, and interviews with experts in Islamic astronomy to assess the validity and relevance of these methods in the modern technological era. The findings reveal that the traditional methods in Maraqil Ubudiyah still hold practical relevance, despite differences from technology-based methods such as digital compass applications and GPS satellites. These findings are expected to enrich the literature on Islamic astronomy and provide a deeper understanding of Qibla direction determination from both Sharia and astronomical perspectives.